2006
DOI: 10.1164/rccm.200601-048oc
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Periodic Acceleration Modifies Experimental Asthma in Sheep

Abstract: Whole-body pGz modulates allergen-induced airway responses in allergic sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…Clinicians hypothesize that percussion and shaking loosen adherent mucus and biofilms from the airway surface, making it easier for cough clearance to remove them from the airways. Alternatively, a number of investigators have shown that mechanical stimulation of certain tissue types results in increased epithelial cell release of NO [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Clinicians hypothesize that percussion and shaking loosen adherent mucus and biofilms from the airway surface, making it easier for cough clearance to remove them from the airways. Alternatively, a number of investigators have shown that mechanical stimulation of certain tissue types results in increased epithelial cell release of NO [4]. …”
Section: Introductionmentioning
confidence: 99%
“…pG z leads to a phosphorylation of eNOS that is correlated with a phosphorylation of Akt in endothelial cells (48). The release of NO into the circulation with pG z has been shown to be physiologically meaningful and long lasting in a sheep model of asthma (1). Additionally, pG z applied to human subjects increases brachial flow-mediated vasodilation and induces release of NO, which is comparable to light to moderate exercise (36,47).…”
mentioning
confidence: 99%
“…N-Nitro-L-arginine methyl ester hydrochloride (L-NAME; Sigma-Aldrich, St. Louis, MO) was given as an intravenous injection; the dose per animal was 25 mg/kg in 20 ml of 0.9% NaCl as previously described. [19]…”
Section: 0 Methodsmentioning
confidence: 99%
“…[1618] In sheep, this technology modulated antigen induced inflammatory responses such as inhibiting nuclear factor kappa beta activity. [19] The purpose of the current investigation was to determine whether NO delivered via the blood stream could access airway epithelium to increase TMV and provide protection against human neutrophil elastase (HNE) induced slowed MCC. [20, 21]…”
Section: 0 Introductionmentioning
confidence: 99%